Auditory P300 in individuals with high schizotypy: associations of schizotypal traits with amplitude and latency under different oddball conditions - Deng, Jue; Chen, Siwei; Ou, Yuanhua; Zhang, Yuanjun; Lin, Ziyue; Shen, Yane; Ye, Yiduo (Frontiers in Human Neuroscience, 2023)
Background: The aim of this study was to compare the characteristics of auditory P300 between healthy individuals with high and low schizotypal traits, and investigate the relationship between schizotypy and P300 under various oddball conditions. Methods: An extreme-group design was adopted. After screening 1519 young adults using the Schizotypal Personality Questionnaire (SPQ), sixty-three participants were chosen and divided into two groups. Basic demographic information was assessed and matched between groups. Depression and anxiety indexes were evaluated and controlled. The P300 component was evoked by an auditory oddball paradigm with different frequencies and durations. Results: (1) The duration P300 amplitude was significantly weaker in the high schizotypy group than in the control group. (2) In the high schizotypy group, the latency of frequency P300 under large-variant oddball condition was significantly correlated with total SPQ scores and disorganized dimension scores. (3) In the control group, a significantly negative correlation was found between the frequency P300 amplitude and the negative dimension score of SPQ. In addition, a significant negative relationship was found between disorganized dimension scores and the latency of duration P300 latency under large-variant oddball condition. Moreover, a significant negative association was found between the amplitude of duration P300 under small-variant oddball condition and negative factor scores. Conclusion: Healthy individuals with high schizotypal traits were likely to have deficient attention and hypoactive working memory for processing auditory information, especially the duration of sounds. P300 effects were correlated with negative and disorganized schizotypy, rather than positive schizotypy. There were diverse patterns of relationship between schizotypal traits and P300 under different oddball conditions, suggesting that characteristics and parameters of target stimuli should be considered cautiously when implementing an auditory oddball paradigm for individuals with schizophrenia spectrum.